Localized Surface Plasmon Resonance Biosensing with Large Area of Gold Nanoholes Fabricated by Nanosphere Lithography - Zhang Nan; Zhou Xiaodong; Xiang Gansheng (Nanoscale Research Letters, 2010)
Abstract Localized surface plasmon resonance (LSPR) has been extensively studied as potential chemical and biological sensing platform due to its high sensitivity to local refractive index change induced by molecule adsorbate. Previous experiments have demonstrated the LSPR generated by gold nanoholes and its biosensing. Here, we realize large uniform area of nanoholes on scale of cm2 on glass substrate by nanosphere lithography which is essential for mass production. The morphology of the nanoholes is characterized using scanning electron microscope and atomic force microscope. The LSPR sensitivity of the nanoholes to local refractive index is measured to be 36 nm/RIU. However, the chip has demonstrated high sensitivity and specificity in biosensing: bovine serum albumin adsorption is detected with LSPR peak redshift of 27 nm, and biotin-streptavidin immunoassay renders a LSPR redshift of 11 nm. This work forms a foundation toward the cost-effective, high-throughput, reliable and robust chip-based LSPR biosensor.